2020
DOI: 10.1101/2020.07.09.194969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission delays and frequency detuning can regulate information flow between brain regions

Abstract: Brain networks exhibit very variable and dynamical functional connectivity and flexible configurations of information exchange despite their overall fixed structure (connectome). Brain oscillations are hypothesized to underlie time-dependent functional connectivity by periodically changing the excitability of neural populations. In this paper, we investigate the role that the connection delay and the frequency detuning between different neural populations play in the transmission of signals. Based on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…The mechanism for interaction may depend on oscillatory activity. This is ubiquitous throughout the hierarchy, with higher frequencies in the PF cortex (Lundqvist et al, 2020), and it may play a role in changes in functional connectivity between areas depending on the current task (Pariz et al, 2021). The inputs and outputs are fixed, though they may differ in strength with experience.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for interaction may depend on oscillatory activity. This is ubiquitous throughout the hierarchy, with higher frequencies in the PF cortex (Lundqvist et al, 2020), and it may play a role in changes in functional connectivity between areas depending on the current task (Pariz et al, 2021). The inputs and outputs are fixed, though they may differ in strength with experience.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, the use of communication delay among brain areas resulted in a model with better fit when compared to the DBN model without communication lag. These results are in compliance with reported literature which already suggested that communication among brain areas sometimes presents a delay (PARIZ et al, 2021), and this lag organizes the brain network synchronization (PETKOSKI; JIRSA, 2019).…”
Section: The Use Of Multivariatesupporting
confidence: 93%
“…the neurons (NOWAK et al, 2017). Additionally, it is crucial to realize that communication across brain areas requires some time delay (PARIZ et al, 2021), which is necessary for maintaining the brain's health or keeping the pathological network synchronization intact (PETKOSKI; JIRSA, 2019). Based on the physician's observed temporal delay pattern, it is possible to determine the seizure initiation zone during ictal activity (MYERS et al, 2020).…”
Section: List Of Tablesmentioning
confidence: 99%